Short- and long-term effects of whole-body photobiomodulation on pain, functionality, tissue quality, central sensitisation and psychological factors in a population suffering from fibromyalgia: protocol for a triple-blinded randomised clinical trial - Santiago Navarro-Ledesma; Ana Gonzalez-Muñoz; James Carroll; Patricia Burton (SAGE Publishing, 2022)
Background: The development of an integral and global treatment to improve the quality of life in those with fibromyalgia syndrome (FMS) is challenging. The aim of this study is to investigate the impact of whole-body photobiomodulation (PBM) on pain perception, functionality, quality of soft tissue, central sensitisation and psychological factors in patients suffering with FMS. Methods: This study is a randomised, placebo-controlled clinical trial. A total of 44 participants will be recruited in a private care practice and randomised to receive either a whole-body PBM therapy programme or placebo in the same care centre. The parameters of the PBM programme are as follows: wavelengths of red and near-infrared LEDs 50:50 ratio with 660-850 nanometers; fluence of 25.2 J/cm 2 ; treatment time of 1200 s and a total power emitted of 967 W. Treatment sessions will be 3 times weekly for a period of 4 weeks, totalling 12 treatment sessions. Primary outcome will be pain (Numeric Pain Rating Scale; Widespread Pain Index; Symptom Severity Score). Secondary outcomes will be functionality (Fibromyalgia Impact Questionnaire; the Leisure Time Physical Activity Instrument), quality of soft tissue (elastography), central sensitisation (pain pressure threshold and the Autonomic Symptom Profile) and psychological factors (Pain Catastrophising scale, Tampa Scale, Self-Efficacy questionnaire). Assessments will be at baseline (T1), after session 6 (T2), after treatment (T3) and 2 weeks (T4), 3 (T5) and 6 (T6) month follow-up. Discussion: PBM therapy has been shown to reduce pain and inflammation and to increase the rate of tissue repair for a wide range of conditions, but its potential use as a whole-body treatment in FM is yet to be explored. This trial will investigate whether whole-body PBM therapy is effective at reducing pain intensity, improving functionality, quality of soft tissue, central sensitisation symptoms and psychological measurements. Furthermore, 3- and 6-month follow-up will investigate long-term efficacy of this treatment. Trial registration: NCT04248972. Registered on January 29, 2020, https://clinicaltrials.gov/ct2/show/NCT04248972?term=navarro-ledesma+santiago&draw=2&rank=2 .